2021
DOI: 10.1177/17562864211004318
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosing small fiber neuropathy in clinical practice: a deep phenotyping study

Abstract: Background and aims: Small fiber neuropathy (SFN) is increasingly suspected in patients with pain of uncertain origin, and making the diagnosis remains a challenge lacking a diagnostic gold standard. Methods: In this case–control study, we prospectively recruited 86 patients with a medical history and clinical phenotype suggestive of SFN. Patients underwent neurological examination, quantitative sensory testing (QST), and distal and proximal skin punch biopsy, and were tested for pain-associated gene loci. Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 43 publications
3
56
0
3
Order By: Relevance
“…Nevertheless, we have recently shown that CCM can enhance the ability to diagnose small fiber neuropathy. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we have recently shown that CCM can enhance the ability to diagnose small fiber neuropathy. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Moreover, we have shown that CCM has equivalent diagnostic utility to quantitative sensory testing and enhances the diagnosis of small fiber neuropathy. 29 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in patients with SFN we have recently shown that abnormal distal IENFD and neurological examination most frequently re ected small bre disease. However, CCM further enhanced diagnosis, whilst QST, QSART, and proximal IENFD were of lower impact [41].…”
Section: Discussionmentioning
confidence: 93%
“…In a case-control study, 86 patients with SFN underwent neurological examination, quantitative sensory testing, distal and proximal skin punch biopsy, and sub-group of 55 patients additionally underwent pain-related evoked potentials (PREP), corneal confocal microscopy (CCM), and a quantitative sudomotor axon reflex test (QSART). An abnormal distal intraepidermal nerve fiber density (IENFD) (60/86, 70%) and neurological examination (53/86, 62%) identified those with SFN and CCM and/or PREP further increased the proportion of patients identified with SFN to 85%, whilst QST, QSART, and proximal IENFD contributed minimally ( 47 ).…”
Section: Ccm In Peripheral Neuropathiesmentioning
confidence: 99%